Analisis Kebutuhan Kualitas dan Kuantitas Udara Menggunakan Software Ventsim dan Kazemaru pada Tambang Bawah Tanah PT. Dempo Maju Cemerlang, Kabupaten Pesisir Selatan, Sumatera Barat - febri yanda praja; bambang heriyadi (Journals Mining Engineering : Bina Tambang, 2023)
Mine engineers can use simulation software such as VentSim and Kazemaru to optimize airflow within the mine and create effective ventilation systems. Comparative analysis between the two software can provide important information about the strengths and weaknesses of each software when optimizing their underground mine ventilation systems. Reliability, computing speed, ease of use, modeling capabilities, accuracy of simulation results, and technical support are some of the factors one might look at in a comparison between VentSim and Kazemaru. In addition, this analysis may include comparison of features, user interface, ease of use, accuracy of simulation results, and time required to perform simulations. Analysis of the data used is quantitative, based on the theory of calculation. The result is quantitative. The focus of the research is the ventilation system used in the PT Dempo Maju Cemerlang mine pit. Mine pit PT. Dempo Maju Cemerlang requires 28.99 m3/s of total air, but based on the conditions at the time the measurements were made, the required amount of air has not been met. The results of calculating the air quantity of the ventilation system used in PT. Dempo Maju Cemerlang is only 24.97 m3/s. Every mining pit of PT. Dempo Maju Cemerlang has a temperature of 22.5–24.1 °C. Air humidity ranges between 88% and 93%. In the simulations performed with ventsim and kazemaru software, Ventsim excels in several features, including dust distribution, visualization and graphing, ventilation efficiency analysis, financial simulations, and an attractive user interface. Keywords:  Air Demand, Software, Ventilation System